Debt monitoring mechanism in soe's: evidence from Indonesia / Murdifin Azhar and Ira Geraldina - -, Murdifin Azhar; -, Ira Geraldina (UiTM Cawangan Johor, 2020)
This study aims to examine the role of independent boards (commissioners) characteristics in monitoring the impact of debt on value of state-owned enterprises' (SOE's). This study used 125 observations of SOEs that are listed on Indonesia Stock Exchange during the period of 2010-2017 as a final sample. The variable of independent commissioner's characteristics is analysed by identifying whether they have political connection with political party in Indonesia or not and whether they have adequate professional background. Using panel data analysis, the results show that there is a different effect of independent commissioner's characteristics in monitoring the impact of debt on value of SOE's. If independent commissioners do not have political connection, but have adequate professional background, they could conduct debt monitoring effectively, thereby increasing the value of SOE's. On the contrary, if independent commissioners do not have political connection, but also do not have adequate professional background, they could not conduct debt monitoring effectively, thereby decreasing the value of SOEs. The results suggest that the goverment should consider the professional background of independent commissioners who have political connection with the rulling party.